MEKANISME ADAPTASI AKAR DAN SERAPAN FOSFOR SPESIFIK TIGA GENOTIPE KEDELAI SEBAGAI RESPON TERHADAP KEKAHATAN FOSFOR PADA TANAH MASAM - Parpen siregar (UNIVED Press, Universitas Dehasen Bengkulu, 2015)
A research was conducted with aims (1) to identify adaptation mechanisms of new soybean genotypes in utilizing limited P from acid mineral soil: through carbon translocation to root and through absorption of specific P, and (2) to describe the respond of soybean genotype to P fertilization. Treatments, including soybean genotypes (Slamet, 19BE, and 25EC) and P fertilization (0 and 400 mg P kg-1 in form of KH2PO4) were factorially arranged in a Completely Randomized Design with four replications. Soybean was planted in a green house using double pot system. The upper pot was filled with a mixture of sterile soil and volcano sand, and lower pot with non sterilized soil. The evaluation was performed at the end vegetative growth phase (R1). Evaluated variables were dry weight of shoot, root, and plant total, alkaline phosphatase activity, number of nodules, N and P absorption, quality specific P index. Data variation was analyzed by using F-test with degree of fredoom α = 5% and differences among treatments were separated by using Duncan Multiple Range Test (DMRT). The results showed that soybean genotype had different mechanism in using limited P from acid mineral soil. Old genotype (Slamet) had mechanism through increasing alkaline phosphatase and absorption of specific P (P-Al, P-Fe dan P occluded). Genotype 19BE had mechanism through translocation of carbon to root or decreasing of shoot-root ratio; specific P absortion (P-Al dan P-Fe) was limited. Genotype 25EC had only decreased shoot-root ratio and P-Fe absortion mechanism. Fertilization with high P (400 mg kg-1) increased biomass production, number of root nodules, absortion N and P nutrients; however it decreased absorption alkaline-phosphatase activity at soybean rhizosphere at 35 day after planting. Fertilizing high dosage P created biopriming by decreasing the qualtity specific P on soil under 19BE and 25EC genotypes.Keywords : adaptation mechanism, soybean genotypes, acid soil, P acquisition